Should aldosterone suppression tests be conducted during a particular phase of the menstrual cycle, and, if so, which phase? Results of a preliminary study. (3rd February 2015) - Ahmed, Ashraf H.; Gordon, Richard D.; Ward, Gregory; Wolley, Martin; Kogovsek, Cynthia; Stowasser, Michael
Summary Background As renin and aldosterone levels vary during the menstrual cycle, and are critical criteria for interpretation of aldosterone suppression tests to confirm or exclude primary aldosteronism, outcome of testing may vary depending on the menstrual cycle phase. We assessed the effect of timing within the menstrual cycle on levels of renin, aldosterone and female sex steroids during fludrocortisone suppression testing (FST). Methods In 22 women undergoing FST who experienced regular menstrual cycles, renin (measured as both plasma renin activity and direct renin concentration), aldosterone (mass spectrometry) and cortisol, progesterone, oestradiol, LH and FSH (immunoassay) levels were compared, relative to phase of cycle. Aldosterone levels were compared to those in age‐matched males undergoing FST. Results Progesterone (P < 0·0001) and aldosterone (P = 0·006) levels were higher in nine women (after one of 10 was excluded with anovulatory cycle) studied during the luteal phase than in the 12 studied during the follicular phase. All studied during the luteal phase had positive FST, and all three with negative FST were studied during the follicular phase. There were no significant differences in other parameters measured except FSH, which was higher (P = 0·02) during the follicular phase. Aldosterone was higher (P = 0·01) in women studied in the luteal (but not follicular) phase compared to men. Conclusion The menstrual cycle may affect the outcome of FST and other suppression testing used to diagnose primary aldosteronism. Larger patient numbers and preferably restudy of the same patient in both phases should clarify this and determine the optimum time in the cycle for testing.